Gas diffusion electrodes and methods of using same, and co2 electrolytic reduction devices
Patent Information
- Application Number
- CN202580022569.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-27
- Filing Date
- 2025-03-17
- Publication Date
- 2026-10-27
AI Technical Summary
[0014]因此,本发明的目的在于提供一种气体扩散电极,其工业生产率和操作性优异,并且长时间进行CO2的电解还原时的C2H4的法拉第效率也优异。
Smart Images

Figure CN122996230A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to a gas diffusion electrode and its usage method, as well as a CO2 electrolytic reduction apparatus. Background Technology
[0002] CO2 emissions are increasing year by year, becoming a social problem contributing to global warming. To address this issue, CO2 electrolysis reduction technology has attracted attention. In this technology, by passing an electric current through CO2 and H2O under specified conditions, CO2 can be reduced and converted into valuable substances such as methane and ethylene. Furthermore, the use of renewable energy sources such as solar power for the electrolysis reduction of CO2 is expected to contribute to the development of sustainable reaction systems.
[0003] In conventional CO2 electrolytic reduction, electrolytic devices (reaction cells) were used in which the cathode was immersed in an aqueous solution while CO2 dissolved in the solution was supplied to the cathode. However, such electrolytic devices suffer from low reactivity due to limitations in the amount of CO2 that can be dissolved in the aqueous solution. Therefore, in recent years, electrolytic devices have been used that isolate the cathode and anode using a hydroxide ion conducting membrane and use a gas diffusion electrode as the cathode, supplying a gas containing CO2 to this gas diffusion electrode, thereby improving reactivity.
[0004] Furthermore, in the electrolytic reduction of CO2, reactant selectivity becomes particularly important because the products can vary depending on reaction conditions, the electrodes used, etc. In this regard, the use of copper as a catalyst capable of generating hydrocarbons such as methane and ethylene has been proposed. For example, non-patent literature 1 (A. Inoue et al., "Ultra-high-rate CO2 reduction reactions to multicarbon products with a current density of 1.7 A cm⁻¹") -2 "Inneutral electrolytes", EES Catalysis Volume 1, Issue 1, pages 9-16 (2023) discloses a gas diffusion electrode obtained by slurrying copper microparticles as catalysts, coating them onto a carbon sheet, and drying them. In a CO2 reduction cell using this electrode, multi-carbon organic compounds can be synthesized from CO2. Furthermore, Patent Document 1 (Japanese Patent No. 5683883) discloses a cathode electrode comprising a porous body made of copper or a copper alloy. This porous body is an aggregate of granular, rod-shaped, or sheet-like particles with an average diameter of 50 nm or more and 5 μm or less, capable of efficiently generating ethane, ethylene, etc.
[0005] However, the use of porous metal foil as the negative electrode current collector in energy storage devices such as lithium-ion secondary batteries is being studied. For example, Patent Document 2 (WO2011 / 67957) discloses that by metal plating on a cracked release layer, porous metal foil composed of a two-dimensional mesh structure made of metal fibers can be obtained with high productivity and low cost.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent No. 5683883
[0009] Patent Document 2: WO2011 / 67957
[0010] Non-patent literature
[0011] Non-patent literature 1: A. Inoue et al., "Ultra-high-rate CO2 reduction reactions to multicarbon products with a current density of 1.7 A cm-2 in neutralelectrolytes", EES Catalysis Volume 1, Issue 1, pages 9-16 (2023) Summary of the Invention
[0012] As disclosed in Patent Document 1 and Non-Patent Document 1, there are challenges in industrial productivity with electrodes for CO2 electrolytic reduction manufactured by slurrying or sintering copper microparticles. Specifically, the numerous manufacturing processes required make it difficult to achieve uniformity and large-area production. Furthermore, the electrode's susceptibility to breakage limits the device's shape. Moreover, during prolonged electrolytic reduction, the porous structure composed of copper microparticles may experience a gradual agglomeration of the microparticles, leading to decreased reactivity.
[0013] The inventors have obtained the following insights: by using a porous copper foil with multiple openings and an average opening diameter controlled below 300 μm as a gas diffusion electrode, the industrial productivity and operability are excellent, and the Faraday efficiency of C2H4 during long-term electrolytic reduction of CO2 is also excellent.
[0014] Therefore, the purpose of this invention is to provide a gas diffusion electrode that has excellent industrial productivity and operability, and also has excellent Faraday efficiency of C2H4 during long-term electrolytic reduction of CO2.
[0015] According to this disclosure, the following methods are provided.
[0016] [Method 1]
[0017] A gas diffusion electrode, used in CO2 electrolytic reduction.
[0018] The gas diffusion electrode is composed of a porous copper foil with multiple openings, the average opening diameter of which, based on the equivalent circle diameter, is less than 300 μm.
[0019] [Method 2]
[0020] According to the gas diffusion electrode of method 1, the aforementioned average opening diameter is 10 μm or more and 50 μm or less.
[0021] [Method 3]
[0022] According to method 1 or 2, the gas diffusion electrode wherein the aforementioned porous copper foil has an opening ratio of 10% or more.
[0023] [Method 4]
[0024] The gas diffusion electrode according to any one of methods 1 to 3, wherein the aforementioned average opening diameter is 10 μm or more and 30 μm or less.
[0025] [Method 5]
[0026] The gas diffusion electrode according to any one of methods 1 to 4, wherein the aforementioned opening ratio is 15% or more and 30% or less.
[0027] [Method 6]
[0028] According to any one of the gas diffusion electrodes of methods 1 to 5, the aforementioned average opening diameter is 90 μm or more and 110 μm or less, and the aforementioned porous copper foil has an opening ratio of 20% or more and 40% or less.
[0029] [Method 7]
[0030] The gas diffusion electrode according to any one of methods 1 to 6, wherein the thickness of the aforementioned porous copper foil is 1 μm or more and 120 μm or less.
[0031] [Method 8]
[0032] The gas diffusion electrode according to any one of methods 1 to 7 is used to produce C2H4 by the aforementioned CO2 electrolytic reduction.
[0033] [Method 9]
[0034] A method of using a gas diffusion electrode, comprising using the gas diffusion electrode described in any one of methods 1 to 8 to perform CO2 electrolytic reduction.
[0035] [Method 10]
[0036] According to the method of using the gas diffusion electrode described in Method 9, C2H4 is generated by the aforementioned electrolytic reduction of CO2.
[0037] [Method 11]
[0038] The method of using the gas diffusion electrode according to method 9 or 10 includes the following steps:
[0039] The process of supplying CO2 and H2O to the aforementioned gas diffusion electrode; and,
[0040] The process involves the electrolytic reduction of the aforementioned CO2 using copper, which forms the aforementioned gas diffusion electrode, as a catalyst, thereby generating a gas containing C2H4.
[0041] [Method 12]
[0042] A CO2 electrolytic reduction apparatus, comprising a gas diffusion electrode as a cathode according to any one of embodiments 1 to 8. Attached Figure Description
[0043] Figure 1 This is a schematic top view showing one embodiment of a porous copper foil constituting the gas diffusion electrode of the present invention.
[0044] Figure 2 This is a schematic top view illustrating another configuration of the porous copper foil constituting the gas diffusion electrode of the present invention.
[0045] Figure 3 This is a schematic cross-sectional view showing one embodiment of a CO2 electrolytic reduction apparatus equipped with the gas diffusion electrode of the present invention.
[0046] Figure 4 This is a schematic cross-sectional view of a gas-phase half-cell used to determine the Faraday efficiency in the embodiments. Detailed Implementation
[0047] Gas diffusion electrode
[0048] The gas diffusion electrode of the present invention is used for CO2 electrolytic reduction. The gas diffusion electrode is constructed of a porous copper foil. One embodiment of the porous copper foil constituting the gas diffusion electrode is shown below. Figure 1 and 2 .like Figure 1 and Figure 2As shown, the porous copper foil 10 has multiple openings 12. Furthermore, the average opening diameter of the multiple openings 12, based on the equivalent circle diameter, is 300 μm or less. Thus, by using the porous copper foil 10 with multiple openings 12 and an average opening diameter controlled to be 300 μm or less as a gas diffusion electrode, excellent industrial productivity and operability are achieved, and the Faraday efficiency of C2H4 during long-term CO2 electrolytic reduction is also excellent.
[0049] In other words, unlike aggregates of copper particles, copper foil exhibits excellent processability and high shape conformability. Therefore, by using porous copper foil 10, gas diffusion electrodes with desired shapes can be easily fabricated, resulting in excellent operability when applied to CO2 electrolytic reduction apparatuses. Furthermore, since copper foil manufacturing facilitates homogenization and large-area production, the industrial productivity of gas diffusion electrodes constructed from porous copper foil is also excellent. Additionally, as mentioned above, during prolonged electrolytic reduction of porous bodies composed of copper particles, the copper particles gradually aggregate, potentially leading to reduced reactivity. In contrast, the gas diffusion electrode of the present invention, due to the use of porous copper foil 10, does not experience particle aggregation, resulting in excellent long-term stability. In particular, by setting the average opening diameter of the porous copper foil 10 to 300 μm or less, the Faraday efficiency of C2H4 during prolonged CO2 electrolytic reduction becomes excellent. As a specific indicator, when the Faraday efficiency is measured under the conditions shown in the embodiments described later, the Faraday efficiency of C2H4 after 3600 seconds from the start of the electrolytic reduction reaction of CO2 is 1% or more, preferably more than 10%, more preferably more than 15%, further preferably more than 20%, and particularly preferably more than 40%. Therefore, the gas diffusion electrode of the present invention is particularly preferred for producing C2H4 by electrolytic reduction of CO2.
[0050] A typical gas diffusion electrode (cathode electrode) typically comprises a reduction catalyst layer and a gas diffusion layer disposed on one side of the reduction catalyst layer. The gas diffusion layer is a layer that assists in the uniform diffusion of CO2-containing gas to the surface of the reduction catalyst layer. In this respect, in the gas diffusion electrode of the present invention, the porous copper foil 10 functions not only as a reduction catalyst layer but also as a gas diffusion layer. That is, when CO2-containing gas is supplied to the gas diffusion electrode, the gas is uniformly diffused to the electrode surface through the multiple openings 12 of the porous copper foil 10, thereby enabling efficient electrolytic reduction of CO2. Therefore, the gas diffusion electrode (excluding the porous copper foil 10 itself) may also be an electrode without a gas diffusion layer. That is, the gas diffusion electrode may be composed solely of the porous copper foil 10. However, the gas diffusion electrode may further include a gas diffusion layer disposed on one side of the porous copper foil 10. Preferred examples of the gas diffusion layer include membrane filters made of hydrophobic materials such as PTFE, but this is not a limitation.
[0051] The porous copper foil 10 has multiple openings 12, which are through holes (through holes) that allow passage from one surface of the copper foil to another. The openings 12 can be arranged in a regular pattern or irregularly on the surface of the copper foil. The shape of the openings 12 is not particularly limited and can be circular, polygonal, or other irregular shapes. The arrangement pattern of the openings 12 is also not particularly limited and can be an interlaced pattern (e.g., 60° interlacing), a parallel pattern, or other irregular patterns. The porous copper foil 10 can also have multiple openings 12 on a single copper foil. Alternatively, as... Figure 2 As shown, the porous copper foil 10 can also have a two-dimensional network structure composed of multiple copper fibers 11. In this case, high strength can be exhibited by the copper fibers 11 distributed in a two-dimensional network. In any case, the porous copper foil 10 is different from a copper porous body (i.e., an aggregate of copper particles) formed by slurrying or sintering copper powder.
[0052] The average opening diameter of the porous copper foil 10 is 300 μm or less, preferably 10 μm or more and 110 μm or less, more preferably 10 μm or more and 50 μm or less, or 90 μm or more and 110 μm or less, more preferably 10 μm or more and 30 μm or less. In this invention, the average opening diameter refers to the average of the equivalent circular diameters of the plurality of openings 12 of the porous copper foil 10. The average opening diameter of the porous copper foil 10 can be measured according to the steps shown in the embodiments described later.
[0053] The porous copper foil 10 preferably has an opening ratio of 10% or more, more preferably 10% or more and 40% or less, even more preferably 15% or more and 40% or less, and particularly preferably 20% or more and 30% or less. This further improves the Faraday efficiency of C2H4 during long-term electrolytic reduction of CO2. The opening ratio of the porous copper foil 10 can be measured according to the steps shown in the embodiments described later.
[0054] According to a preferred embodiment of the present invention, the average opening diameter of the porous copper foil 10 is 10 μm or more and 50 μm or less, and the opening ratio is 10% or more; more preferably, the average opening diameter is 10 μm or more and 30 μm or less, and the opening ratio is 10% or more; even more preferably, the average opening diameter is 10 μm or more and 30 μm or less, and the opening ratio is 15% or more and 30% or less. Furthermore, according to another preferred embodiment of the present invention, the average opening diameter of the porous copper foil 10 is 90 μm or more and 110 μm or less, and the opening ratio is 20% or more and 40% or less. This further improves the Faraday efficiency of C2H4 during long-term electrolytic reduction of CO2.
[0055] The thickness of the porous copper foil 10 is preferably 1 μm or more and 120 μm or less, more preferably 1 μm or more and 50 μm or less, even more preferably 1 μm or more and 35 μm or less, and particularly preferably 1 μm or more and 18 μm or less. This allows for a balanced achievement of high strength and excellent processability. The thickness of the porous copper foil 10 can be measured according to the steps shown in the embodiments described later.
[0056] The manufacturing method of the porous copper foil 10 constituting the gas diffusion electrode is not particularly limited, and it can be manufactured by any method. For example, as disclosed in Patent Document 2 (WO2011 / 67957), a release layer is formed on a conductive substrate, cracks are generated in the release layer, and then electrolytic copper plating is performed on the cracked release layer, thereby preferably forming a porous copper foil 10 having a two-dimensional network structure composed of copper fibers 11. Preferred conditions for electrolytic copper plating are described below.
[0057] The following describes another example of a preferred manufacturing method for the porous copper foil 10. First, a support for manufacturing the porous copper foil is prepared. When manufacturing the porous copper foil 10 by electrolytic copper plating, the support can be any substrate with conductivity sufficient for plating; inorganic materials, organic materials, laminates, and materials with a metallic surface can all be used, but metals are preferred. Preferred examples of such metals include copper, nickel, cobalt, iron, chromium, tin, zinc, indium, silver, gold, aluminum, and titanium, as well as alloys containing at least one of these metallic elements; copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, and stainless steel are more preferred. However, when manufacturing the porous copper foil by chemical copper plating, the support can also be a non-conductive substrate.
[0058] Multiple plating masks (e.g., photoresist) are formed on the prepared support surface. The areas covered by these plating masks correspond to the openings 12 in the porous copper foil 10. Therefore, by adjusting the size of the plating masks and their coverage of the support surface, the average opening diameter and opening ratio of the porous copper foil 10 can be controlled. The size (equivalent circle diameter) of each plating mask is preferably 5 μm or more and 330 μm or less, more preferably 5 μm or more and 120 μm or less, and even more preferably 5 μm or more and 35 μm or less. The coverage of the plating masks on the support surface is preferably 1% or more and 60% or less, more preferably 10% or more and 35% or less. Furthermore, by changing the shape and arrangement pattern of each plating mask, the shape and pattern of the openings 12 in the porous copper foil 10 can be controlled. The shape of each plating mask is not particularly limited and can be circular, polygonal (e.g., quadrilateral), or any other arbitrary shape. The arrangement pattern of the coating mask is not particularly limited; for example, staggered patterns (e.g., 60° staggered) or side-by-side patterns can be used. The type and formation method of the coating mask are not particularly limited; for example, it can preferably be formed by laminating a photosensitive resin onto the surface of a support and then exposing and developing it in a predetermined pattern. Alternatively, an insulating layer made of an insulating inorganic material such as DLC (diamond-like carbon) can be formed on the surface of the support in a predetermined pattern. The coating mask can be directly formed on the surface of the support using various printing methods such as inkjet printing.
[0059] Copper plating is performed on a support with a plating mask. After removing the plating mask as needed, the copper plating is peeled off from the support, thereby forming a porous copper foil 10 with multiple openings 12. The copper plating can be either electrolytic copper plating or chemical copper plating, preferably electrolytic copper plating. This electrolytic copper plating preferably uses a solution with a copper concentration of 5 g / L or more and 200 g / L or less (more preferably 10 g / L or more and 100 g / L or less, even more preferably 15 g / L or more and 30 g / L or less), a sulfuric acid concentration of 50 g / L or more and 260 g / L or less (more preferably 60 g / L or more and 230 g / L or less, even more preferably 150 g / L or more and 230 g / L or less), at a solution temperature of 10°C or more and 50°C or less (more preferably 20°C or more and 45°C or less, even more preferably 20°C or more and 30°C or less), and a current density of 0.5 A / dm³. 2 Above and 50A / dm 2 Below (more preferably 1.0A / dm) 2 Above and 30.0A / dm 2 The following is a further preferred option: 1.0 A / dm 2 Above and 10A / dm 2 Under the following conditions, a porous copper foil with a specified average opening diameter and opening ratio can be easily formed. The porous copper foil 10 thus obtained can be used directly as a gas diffusion electrode, or it can be processed using known methods to form a gas diffusion electrode with a desired shape.
[0060] From the viewpoint of efficiently generating C2H4 during CO2 electrolytic reduction, the surface of the porous copper foil 10 preferably exposes copper. Therefore, if the surface of the porous copper foil 10 has an oxide coating, anti-rust coating, etc., it is preferable to remove these coatings. Examples of removal methods include grinding, pickling, and electro-cleaning.
[0061] How to use a gas diffusion electrode
[0062] The gas diffusion electrode of the present invention is preferably used for CO2 electrolytic reduction. That is, according to a preferred embodiment of the present invention, a method of using a gas diffusion electrode is provided, which includes performing CO2 electrolytic reduction using the gas diffusion electrode described above. The method of using the gas diffusion electrode in this embodiment preferably generates C2H4 by CO2 electrolytic reduction. Specifically, the method of using the gas diffusion electrode preferably includes the following steps: (1) a step of supplying CO2 and H2O to the gas diffusion electrode; and (2) a step of performing CO2 electrolytic reduction. Hereinafter, steps (1) and (2) will be described.
[0063] (1) Supply of CO2 and H2O
[0064] In this process, CO2 and H2O are supplied to the gas diffusion electrode. The supply of CO2 to the gas diffusion electrode is preferably carried out using a gas containing 50% or more (more preferably 99% or more) CO2, under conditions of 0°C or higher and 90°C or lower. The gas may also be humidified before being supplied to the electrode. On the other hand, the supply of H2O to the gas diffusion electrode is preferably carried out via a hydroxide ion conducting membrane permeable to H2O, as described later with respect to the CO2 electrolysis reduction apparatus. That is, by supplying a gas containing water vapor to the anode, H2O passes through the anode and the hydroxide ion conducting membrane and reaches the surface of the gas diffusion electrode. Alternatively, the supply of H2O to the gas diffusion electrode can also be carried out by contacting one side of the gas diffusion electrode with the electrolyte. The type of electrolyte is not particularly limited; for example, an aqueous solution of KHCO3, particularly a 1 mol / L aqueous solution of KHCO3, is preferably used. The electrolyte, such as the aqueous solution of KHCO3, is preferably pre-saturated with CO2. This effectively suppresses the dissolution of CO2 in the gas phase into the electrolyte.
[0065] (2) Electrolytic reduction of CO2
[0066] In this process, CO2 is electrolytically reduced using copper as a catalyst, which constitutes the gas diffusion electrode. This generates a gas containing C2H4. The electrolytic reduction of CO2 can be carried out, for example, by applying a predetermined voltage to the gas diffusion electrode. That is, by supplying CO2 and H2O, the reduction reaction of CO2 is carried out. The applied voltage, based on the reversible hydrogen electrode potential, is preferably -3.0V or higher and 0.0V or lower; more preferably -2.0V or higher and 0.0V or lower, and even more preferably -2.0V or higher and -1.0V or lower, to obtain high Faradaic efficiency. On the other hand, to obtain high overall battery efficiency, the above-mentioned applied voltage is preferably -1.0V or higher and 0.0V or lower.
[0067] CO2 electrolytic reduction device
[0068] The gas diffusion electrode of the present invention is preferably used as the cathode of a CO2 electrolysis reduction apparatus. That is, according to a preferred embodiment of the present invention, a CO2 electrolysis reduction apparatus comprising a gas diffusion electrode as the cathode is provided. A preferred embodiment of the CO2 electrolysis reduction apparatus of this embodiment is shown below. Figure 3 . Figure 3The CO2 electrolysis reduction apparatus 100 shown includes a cathode 102, an anode 104, and a hydroxide ion conducting membrane 106. The cathode 102 is the gas diffusion electrode described above. The anode 104 is disposed opposite to the cathode 102. The anode 104 typically includes a catalyst layer and a gas diffusion layer. The hydroxide ion conducting membrane 106 isolates the cathode 102 and the anode 104 in a manner that allows hydroxide ions to conduct while allowing H2O to pass through. The hydroxide ion conducting membrane 106 is, for example, made of a solid electrolyte. The CO2 electrolysis reduction apparatus 100 preferably also includes an external power supply 108 for applying a predetermined voltage to the cathode 102 and the anode 104. The CO2 electrolysis reduction apparatus 100 preferably also includes a flow path for supplying a gas containing CO2 to the cathode 102, and a flow path for discharging the gas supplied for the reduction reaction based on the cathode 102 along with the reaction product gas. Similarly, the CO2 electrolytic reduction apparatus 100 preferably also includes a flow path for supplying a gas containing water vapor to the anode 104, and a flow path for discharging the gas supplied for the oxidation reaction based on the anode 104 together with the reaction-generated gas. In any case, the CO2 electrolytic reduction apparatus 100 may employ a known configuration other than including the gas diffusion electrode described above as the cathode 102.
[0069] Example
[0070] The invention is illustrated more specifically by the following examples. However, the invention is not limited to these examples.
[0071] Example 1
[0072] The porous copper foil was fabricated as follows. First, a 35 μm thick copper foil was prepared as the conductive substrate. Chromium plating was then applied to this copper foil as a release layer, following these steps: The copper foil was immersed for 2 minutes at 40°C in an acidic cleaning agent for printed wiring boards (manufactured by Murata Co., Ltd., PAC-200) adjusted to 120 ml / L with added water. The cleaned copper foil was then acid-activated by immersing it in 50 ml / L sulfuric acid at room temperature for 1 minute. The acid-activated copper foil was then immersed in a chromium plating bath containing 180 g / L Econom 300 (manufactured by Meltex, Inc.) and 1 g / L purified concentrated sulfuric acid at a temperature of 50°C and a current density of 20 A / dm³. 2 Chromium plating was performed under specific conditions. The copper foil with chromium plating was then washed and dried. The thickness of the chromium plating was determined by XRF (X-ray fluorescence analysis), and the result was approximately 3 μm. Numerous cracks, believed to be caused by plating stress, were confirmed on the surface of the chromium plating.
[0073] Copper sulfate plating was performed on the chromium plating where the crack occurred. This copper sulfate plating was carried out by immersing the chromium-plated copper foil in a copper sulfate plating bath containing 250 g / L copper sulfate pentahydrate (copper concentration approximately 64 g / L) and 80 g / L sulfuric acid, at a current density of 20 A / dm³. 2 The process was carried out under the following conditions: anode: DSE (insoluble electrode for oxygen evolution); bath temperature: 40°C. At this temperature, copper particles grew from the cracks because current flowed more easily in the cracked areas than on the outermost surface of the chromium plating. As a result, a two-dimensional network structure of copper fibers was formed on the chromium plating, resulting in a porous copper foil of a specified thickness. The porous copper foil was physically peeled off from the chromium plating to obtain the separated porous copper foil. The separated porous copper foil was then heated at 200°C under vacuum for 1 hour to straighten its curling. The surface of the porous copper foil was then acid-washed to prepare an evaluation sample.
[0074] Examples 2 to 11
[0075] A dry film (manufactured by Hitachi Chemicals Co., Ltd., RY-3625) was thermally laminated onto a titanium electrode. This thermal lamination was performed at a temperature of 110°C, a pressure of 0.4 MPa, and a conveying speed of 0.5 m / min. The dry film on the electrode was exposed and developed using a 60° staggered pattern of circular dots, thereby forming a plating mask (resist). The pattern was adjusted so that the dot diameter and coverage of the plating mask on the electrode surface were the values shown in Table 1. The electrode with the plating mask formed was immersed in a copper sulfate plating bath containing 75 g / L copper sulfate pentahydrate (approximately 19 g / L based on copper concentration) and 220 g / L sulfuric acid, at a current density of 2 A / dm³. 2 Under conditions of DSE (insoluble electrode for oxygen evolution) anode and bath temperature of 25°C, a current was applied to achieve a specified thickness. This resulted in copper plating on the portion of the electrode where the plating mask was not formed. For the electrode after copper plating, the plating mask was peeled off using a stripping solution (Mitsubishi Gas Chemical Co., Ltd., R-100S) at 50°C, thereby obtaining a porous copper foil with openings in the portion where the plating mask was formed. The porous copper foil was then physically peeled off from the electrode, resulting in a separated porous copper foil. The separated porous copper foil was heated at 200°C under vacuum for 1 hour to correct its curling, and then its surface was acid-washed to prepare an evaluation sample.
[0076] Example 12 (Compare)
[0077] A commercially available porous copper foil with multiple openings was prepared, and the surface of the porous copper foil was electrically cleaned in 85% H3PO4 to produce an evaluation sample.
[0078] [Table 1]
[0079]
[0080] evaluate
[0081] The porous copper foils produced in Examples 1 to 12 were evaluated in various ways as shown below.
[0082] (a) Determination of average opening diameter and opening ratio
[0083] For the precipitated surfaces of porous copper foil, observations were performed using an optical microscope (KEYENCE CORPORATION, VHX-8000) with the following settings: light source: ring illumination, shutter speed: automatic 25, gain: manual 0dB, and magnification: 100x. Next, the image was binarized from the observed image using the automatic area measurement (particle counting) function, and the average aperture diameter and aperture ratio were measured. Image brightness was selected as the extraction method, and the darker areas were extracted as apertures with brightness adjustment: -25 and brightness unevenness removal (strong) settings. No image adjustments were made to the extracted apertures. Then, for the extracted apertures, the average equivalent circle diameter was taken as the average aperture diameter, and the total area ratio was taken as the aperture ratio. The results are shown in Table 2.
[0084] (b) Thickness measurement
[0085] The thickness of the porous copper foil was measured using a microscope as follows: First, to prevent deformation due to cutting stress, the porous copper foil was coated with resin. The resin-coated porous copper foil was then cut along the thickness direction using a slicer (Leica RM2265). Next, the thickness of the cut surface of the porous copper foil was measured at three points using a microscope (Leica DM LM) at a magnification of 20x. The average value was taken as the thickness of the porous copper foil. The results are shown in Table 2.
[0086] (c) Determination of Faraday efficiency
[0087] To evaluate Faraday efficiency, a [structure / mechanism] was constructed. Figure 4The gas-phase half-cell 200 is shown. The gas-phase half-cell 200 includes: a tank 202; an electrolyte 204 injected into the tank 202; a working electrode 206 forming the bottom of the tank 202 in contact with the electrolyte 204; a PTFE membrane filter (pore size: 0.45 μm) 207 disposed on the side of the working electrode 206 opposite to the electrolyte 204; a counter electrode 208 and a reference electrode 210 immersed in the electrolyte 204; a supply pipe 212a for supplying gas to the working electrode 206; and a recovery pipe 212b for recovering the supplied gas and the gas generated during the reduction reaction. The specific configurations of the electrolyte 204, working electrode 206, counter electrode 208, and reference electrode 210 are described below.
[0088] - Electrolyte 204: 1M aqueous solution of KHCO3 saturated with CO2.
[0089] -Working electrode 206: Porous copper foil with a diameter of approximately 3 cm (evaluation sample)
[0090] - Counter electrode 208: carbon rod
[0091] -Reference electrode 210: Ag / AgCl
[0092] Under the following conditions, gas is supplied from the supply pipe 212a of the gas phase half-cell 200, causing the reduction reaction of carbon dioxide to occur at -1.4V. RHE The reduction reaction is carried out under these conditions for 3600 seconds.
[0093] <Gas Supply Conditions>
[0094] Composition: CO2 (99.99% purity)
[0095] - Flow rate: 5 mL / min
[0096] Temperature: 25℃
[0097] - Humidification: Dry
[0098] The above-mentioned supply gas and the gas generated during the reduction reaction are recovered using recovery tube 212b and directly supplied to the gas chromatograph, thereby analyzing the reaction products at any time point during the voltage application process.
[0099] <Analysis Conditions>
[0100] - Apparatus: Gas chromatograph (Shimadzu Corporation, GC-2030)
[0101] - Detector: Barrier Discharge Ionization Detector (BID) (Shimadzu Corporation, GC-2030 built-in option)
[0102] - Column: Made by Shinwa Chemical Co., Ltd., Micropacked-ST, 1.0m in length, 1.0mm in inner diameter.
[0103] - Sample injection method: split method (split ratio 4:1)
[0104] - Sample injection volume: 1 mL (based on online measurement of carbon dioxide gas flowing in at a rate of 5 mL / min for the reaction)
[0105] - Inlet temperature: 150℃
[0106] - Detector temperature: 280℃
[0107] Based on the analysis results of gas chromatography, ethylene was detected as a product in Examples 1-11, while no ethylene was detected in Example 12. For the detected ethylene, the amount of substance produced was determined, and the Faraday efficiency after 3600 seconds from the start of the reduction reaction was calculated using the following formula.
[0108] FE=100×z×n×F / Q
[0109] (In the formula, FE represents the Faraday efficiency (%), z represents the number of electrons required to form one molecule of product, n represents the number of moles of product (mol), F represents the Faraday constant (96486 C / mol), and Q represents the amount of charge flowing through (C))
[0110] The results are shown in Table 2. It should be noted that the charge Q can be calculated by detecting the current I flowing under a specified voltage and multiplying it by a specified application time t (=I×t). Furthermore, the number of electrons z in ethylene is as follows.
[0111] - Ethylene (z=12): CO2 + 12H + +12e - →C2H4+4H2O
[0112] [Table 2]
[0113]
[0114] Explanation of reference numerals in the attached figures
[0115] 10 Porous copper foil
[0116] 11 Copper Fiber
[0117] 12. Opening
[0118] 100 CO2 Electrolytic Reduction Unit
[0119] 102 Cathode
[0120] 104 Anode
[0121] 106 Hydrogen-oxygen ion conducting membrane
[0122] 108 External Power Supply
[0123] 200 gas phase half-cell
[0124] 202 slot
[0125] 204 Electrolyte
[0126] 206 Working electrode
[0127] 207 Membrane Filter
[0128] 208 pairs of electrodes
[0129] 210 Reference Electrode
[0130] 212a Supply Pipe
[0131] 212b Recycling tube.
Claims
1. A gas diffusion electrode, used in CO2 electrolytic reduction, The gas diffusion electrode is composed of a porous copper foil with multiple openings, the average opening diameter of which, based on the equivalent circle diameter, is less than 300 μm.
2. The gas diffusion electrode according to claim 1, wherein, The average opening diameter is greater than 10 μm and less than 50 μm.
3. The gas diffusion electrode according to claim 2, wherein, The porous copper foil has an opening ratio of more than 10%.
4. The gas diffusion electrode according to claim 3, wherein, The average opening diameter is greater than 10 μm and less than 30 μm.
5. The gas diffusion electrode according to claim 4, wherein, The opening ratio is 15% or more and 30% or less.
6. The gas diffusion electrode according to claim 1, wherein, The average opening diameter is 90 μm or more and 110 μm or less, and the porous copper foil has an opening ratio of 20% or more and 40% or less.
7. The gas diffusion electrode according to claim 1, wherein, The thickness of the porous copper foil is greater than 1 μm and less than 120 μm.
8. The gas diffusion electrode according to any one of claims 1 to 7, used to produce C2H4 by electrolytic reduction of CO2.
9. A method of using a gas diffusion electrode, comprising performing CO2 electrolytic reduction using the gas diffusion electrode according to any one of claims 1 to 7.
10. The method of using the gas diffusion electrode according to claim 9, wherein, C2H4 is generated by the electrolytic reduction of CO2.
11. The method of using the gas diffusion electrode according to claim 9, comprising the following steps: The process of supplying CO2 and H2O to the gas diffusion electrode; and, The process involves the electrolytic reduction of CO2 using copper, which forms the gas diffusion electrode, as a catalyst, to generate a gas containing C2H4.
12. A CO2 electrolytic reduction apparatus, comprising a gas diffusion electrode as a cathode according to any one of claims 1 to 7.
Citation Information
Patent Citations
Semiconductor storage device
JP1981083883A
Porous metal foil and method for manufacturing the same
WO2011067957A1